Analisis Mutu Minyak Zaitun Yang Diperoleh Dari Buah Zaitun (Olea eurofaea) Dan Aplikasinya Sebagai Antikolesterol - Duwi Cahyadi, Kadek; Dewi Lestari, Gusti Ayu; Esati, Ni Ketut (Universitas Negeri Gorontalo, 2023)
Olive oil is oil obtained from olives (Olea europaea L.). Olive oil contains high in oleic acid so it can be used as an anticholesterol. This study aims to determine the quality of olive oil according to SNI 01-4474-1998 and its anticholesterol activity by UV-Vis spectrophotometry. In this research, olive oil quality test was conducted, namely water content test using the thermogravimetric method, fatty acid content test using an alkalimetric titration method based on an acid-base reaction, saponification test using the acidimetric method, and iodine number test using the iodometric titration method. The method of testing the anticholesterol activity of olive oil was carried out in vitro using Lieberman-Burchard reagent. The results of the quality test on olive oil obtained water content of 0.03%, free fatty acids 1.73%, saponification number 190.90 mgKOH/g, iodine number 91.25g iodine/100g, where these results have met the SNI 01-4474-1998 standard. The results of the anticholesterol test showed a decrease in free cholesterol levels by 39.76%. Olive oil shows anticholesterol activity due to the presence of oleic acid or MUFA (Mono Unsaturated Fatty Acids)